The modal analysis and steady-state response in vibration transportation mechanism of rice seeding thrower - LI Jian-ping; ZANG Shao-feng (浙江大学学报. 农业与生命科学版)
In this paper, a detailed finite element model about vibration transportation machine of rice seeding thrower is established. The model and steady-state response of the vibration system are analyzed in the field, and the frequency, modal type and swing of the model are confirmed. The whole analysis is completed in computer, so that repeated experimentation necessary for traditional design is dispensable and a new thinking mode of design is embodied.